Impact of microelectrode recording guided targeting on final position of DBS electrodes in patients with Parkinson’s disease - บุญญวงศ์, แพ่งภูมิ; บุณยะรัตเวช, กฤษณพันธ์ (Thai Journal of Neurological Surgery, 2025)
Objectives: The clinical results of deep brain stimulation (DBS) of the subthalamic nucleus (STN) and internal globus pallidus (Gpi) are highly dependent on accurate targeting and target implantation. Several targeting techniques are in current use, including image-only and/or electrophysiologically guided approaches using microelectrode recordings (MERs). The purpose of this study was to make an appraisal of imaging only based versus imaging with the intraoperative MERs guided electrode targeting. Material and Methods: The authors evaluated patients undergoing DBS between January 2011 and December 2018. The position of the STN and Gpi target was estimated from preoperative MR images with relation to the position of the midcommissural point. MERs were obtained for each trajectory. The authors compared the image-based target with the final coordinates of the electrodes as seen on postoperative CT. Accuracy was assessed by both vector error and trajectory radial error. Results: Fifty three patients underwent the procedure. One hundred and six electrodes were placed (all bilateral). Electrode implant locations were the STN and Gpi in 39 and 14 patients, respectively. Target accuracy measurements were as follows: Median vector error 2.28mm (IQR; 1.47,3.17) and median trajectory radial error 0.7mm (IQR; 0.3,1.5). There was a statistically significant (positive) correlation between two error (r=0.538, p < 0.001) Conclusions: The imaging only based targeting compared with final coordinates of the electrodes from intraoperative MER guided targeting as seen on postoperative CT had median vector error 2.28mm (IQR; 1.47,3.17)